Remyelination in multiple sclerosis from the miRNA perspective - Maciak, Karina; Dziedzic, Angela; Saluk, Joanna (Frontiers in Molecular Neuroscience, 2023)
Remyelination relies on the repair of damaged myelin sheaths, involving microglia cells, oligodendrocyte precursor cells (OPCs), and mature oligodendrocytes. This process drives the pathophysiology of autoimmune chronic disease of the central nervous system (CNS), multiple sclerosis (MS), leading to nerve cell damage and progressive neurodegeneration. Stimulating the reconstruction of damaged myelin sheaths is one of the goals in terms of delaying the progression of MS symptoms and preventing neuronal damage. Short, noncoding RNA molecules, microRNAs (miRNAs), responsible for regulating gene expression, are believed to play a crucial role in the remyelination process. For example, studies showed that miR-223 promotes efficient activation and phagocytosis of myelin debris by microglia, which is necessary for the initiation of remyelination. Meanwhile, miR-124 promotes the return of activated microglia to the quiescent state, while miR-204 and miR-219 promote the differentiation of mature oligodendrocytes. Furthermore, miR-138, miR-145, and miR-338 have been shown to be involved in the synthesis and assembly of myelin proteins. Various delivery systems, including extracellular vesicles, hold promise as an efficient and non-invasive way for providing miRNAs to stimulate remyelination. This article summarizes the biology of remyelination as well as current challenges and strategies for miRNA molecules in potential diagnostic and therapeutic applications.